1995
DOI: 10.1128/aem.61.8.3024-3030.1995
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptides are the main source of nitrogen for Lactococcus lactis during growth in milk

Abstract: The consumption of amino acids and peptides was monitored during growth in milk of proteinase-positive (Prt ؉) and-negative (Prt ؊) strains of Lactococcus lactis. The Prt ؊ strains showed monophasic exponential growth, while the Prt ؉ strains grew in two phases. The first growth phases of the Prt ؉ and Prt ؊ strains were the same, and no hydrolysis of casein was observed. Also, the levels of consumption of amino acids and peptides in the Prt ؉ and Prt ؊ strains were similar. At the end of this growth phase, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
12

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(98 citation statements)
references
References 40 publications
5
81
0
12
Order By: Relevance
“…However, none of the amino acids were completely utilized, when bacterial growth stopped, indicating that some other compound(s) were lacking in the medium. Similar results were reported by Juillard et al (1995) for L. lactis growing in milk. As the greatest amount of amino acid utilization was observed in the presence of both dipeptides (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…However, none of the amino acids were completely utilized, when bacterial growth stopped, indicating that some other compound(s) were lacking in the medium. Similar results were reported by Juillard et al (1995) for L. lactis growing in milk. As the greatest amount of amino acid utilization was observed in the presence of both dipeptides (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…While many anaerobic bacteria utilize sugars in the ways described above, lactococci and streptococci are unique in their avoidance of de novo synthesis of many macromolecular building blocks, especially amino acids (Juillard et al, 1995;Poolman & Konings, 1988). These bacteria therefore make great nutritional demands on the growth medium, which are accommodated by a wide variety of substrate transporters (Poolman, 1993).…”
Section: Proton Motive Force Generation By the F1fo Atpase And Solutementioning
confidence: 99%
“…This genetic element is normally not present in the dairy-derived strains and is spontaneously lost upon prolonged growth of L. lactis KF147 in milk (Bachmann, 2009). Milk contains very low amounts of free amino acids and peptides, and L. lactis ssp., having low amino acid biosynthetic capabilities, may depend on a proteolytic system that allows the degradation and utilization of the predominant protein in bovine milkcasein (Mills & Thomas, 1981;Juillard et al, 1995). Casein contains all the amino acids necessary for the growth of L. lactis.…”
Section: Plasmid-borne Genes and Horizontal Gene Transfermentioning
confidence: 99%
“…As growth media ingredients, YE have been shown to stimulate growth of lactic acid bacteria . Amino acids (Benthin and Villadsen, 1996;Juillard et al, 1995), nucleotides and inorganic constituents have been shown to be growth stimulators for lactococci . Autolysates and yeasts extracts are used in culture media at Ͻ10 g/L, but yeast extract solutions obtained at the end of the autolytic process have Ͼ70 g/L soluble solids.…”
Section: Introductionmentioning
confidence: 99%